Dual‐band modified rectangular shaped dielectric resonator antenna with diversified polarization feature. (7th July 2021) - Dwivedi, Ajay Kumar; Sharma, Anand; Ranjan, Pinku
Abstract: In this communication, the aperture coupled modified rectangular dielectric resonator antenna (rDRA) is designed and studied. The modified rectangular DRA is the same as Swastik shape. An asymmetrical microstrip line‐fed aperture stimulated a triple radiating mode pattern inside the ceramic material, that is, TE 111, TE 211 x and TE 121 y, respectively. Swastik‐shaped ceramic radiator provides two important advantages: (a) lower Q‐factor, which in turn improves the impedance bandwidth, and (b) the creation of degenerated orthogonal mode with 90° phase shifts, which provides CP waves in one of the operating bands. Experimental outcomes confirm that the proposed antenna is working in dual‐frequency bands, that is, 6.41–7.38 GHz and 10.2–12.8 GHz, respectively. It supports left‐handed CP waves from 11.51 to 11.89 GHz. The proposed antenna is widely employable for fixed service satellite (FSS) for defense applications. Abstract : In this communication, aperture coupled modified rectangular dielectric resonator antenna is designed. The modified rectangular DRA is the same as Swastik shape. Three distinct radiating mode patterns were generated inside the ceramic material, that is, TE 111, TE 211 x and TE 121 y . The advantages of the proposed design are as follows: (a) lower Q‐factor, which improves the impedance bandwidth, and (b) the creation of degenerated orthogonal mode with 90° phase shifts, which provides CP wave.